A research on individual innovativeness levels of football referees (Kocaeli region case) - Kursad Sertbas; Levent Atalı (Türk Spor ve Egzersiz Dergisi)
The aim of this research is determining innovativeness levels of football referees in Kocaeli Region, defining their differences in terms of age, education and term of refereeing and discussing such differences within the scope of literature. The sample group of the research is composed of 132 football referees selected by convenience sampling method. “Individual Innovativeness Scale” was used for determining innovativeness levels of football referees. Besides, personal information section was attached to the scale to obtain demographic data of the sample group. In data evaluation, one-way analysis of variance was used since the scores of dependent variables are distributed both homogenously and normally and since the number of groups was more than two and Levene's test was used concerning the variance homogeneity. In this research, it was determined that individual innovativeness levels of football referees were included in the “early majority” category at the rate of 44% and in the “early adopters” category at the rate of 34%. No football referee was included in the “laggards” category comprising the people who are biased towards change and who adopt the innovations later than anyone. Moreover, no significant difference was found between the individual innovativeness scores of football referees and the variables of age, education and term of refereeing (p gt;.05). As a result, it can be said that planning according to different variables other than age, educational background and term of refereeing will be more beneficial and appropriate in realization of new implementation and practices for football referees in the future. It must not be ignored that generalization made for all football referees has some limitations according to the data obtained as a result of this study.